2007
DOI: 10.1007/s11199-006-9159-z
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Young Adulthood: The Moderating Influences of Gender-related Personality Traits and Coping Flexibility

Abstract: The study was designated to explore the resilient (moderating) influences of gender-related personality traits and coping flexibility on the relations between life event stress and psychosocial adjustment in a sample of 291 Chinese young adults. Multiple outcomes (i.e., psychological, physical, and interpersonal aspects of adjustments) were separately examined with regression analysis. The interaction effects explained 5% of the unique variance in the psychological distress model and 4% of the unique variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 73 publications
7
67
2
5
Order By: Relevance
“…The methodology and results of our research show similarity with works in which (1) safety is a term that integrates the ideas of well-being, sustainability, and equal access to resources (hong & Eamon, 2012) and (2) the concept of safety correlates with the results of studies of individual resilience and hardiness (Lam & McBride-Chang, 2007;Maddi, 2002). We took this work into account in our studies, but at the same time, in contrast with foreign researchers and practitioners, we added both the sociopsychological factors that provide safety in the educational environment and an assessment of the level of psychological safety.…”
Section: Discussionsupporting
confidence: 52%
“…The methodology and results of our research show similarity with works in which (1) safety is a term that integrates the ideas of well-being, sustainability, and equal access to resources (hong & Eamon, 2012) and (2) the concept of safety correlates with the results of studies of individual resilience and hardiness (Lam & McBride-Chang, 2007;Maddi, 2002). We took this work into account in our studies, but at the same time, in contrast with foreign researchers and practitioners, we added both the sociopsychological factors that provide safety in the educational environment and an assessment of the level of psychological safety.…”
Section: Discussionsupporting
confidence: 52%
“…Research focusing on individual analysis (i.e., Dumont & Provost, 1999;Lam & McBride-Chang, 2007;Ong, Bergeman, Bisconti & Wallace, 2006) often ignored the broader context in which development occurs. Likewise, research on socialenvironmental factors (i.e., Bonanno et al, 2007) has not considered individual factors.…”
Section: The Present Studymentioning
confidence: 99%
“…The scale has an acceptable validity and test-retest reliability (Brand & Johnson, 1982). Lam and McBride-Chang (2007) reported the scale's α as 0.93. In the present study, the Cronbach alpha value was 0.93.…”
Section: Stressorsmentioning
confidence: 99%
“…More recently, studies have explored the moderating role of gender role orientation with ethnically-diverse samples. For example, Lam and McBride-Chang (2007) found that a greater masculine role orientation reduced the negative impact of stress on interpersonal functioning among Chinese American adolescents. Still, no known studies have explored the extent to which gender role orientation may moderate the association between daily hassles and African American adolescent females' psychological outcomes.…”
Section: Daily Hassles and African American Adolescent Females' Psychmentioning
confidence: 99%